Peran Guru Madrasah Diniyah dalam Mengcegah dan Menangani Bullying di Pondok Pesantren Al-Qodiriyah Tahun Ajaran 2024-2025 - Imroatul A’la; Hadiqoh Asmuni; Mursidah Mursidah (CV. Lentera Literasi Indonesia, 2026)
This study aims to examine the role of Madrasah Diniyah teachers in preventing and handling bullying, the forms of education they provide, and their efforts to build a positive environment at Al-Qodiriyah Islamic Boarding School in 2024-2025. The study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Data were analyzed interactively through the stages of data reduction, presentation, and conclusion drawing, and their validity was tested through triangulation. The results indicate that Madrasah Diniyah teachers play a strategic role in preventing and managing bullying through instilling moral values, modeling exemplary behavior, emotional approaches, and various educational strategies such as anti-bullying socialization, moral lessons, thematic sermons, visual campaigns, and dialogue forums. Furthermore, the teachers actively foster a positive, safe, and conducive boarding school environment, supporting the development of students’ character to be respectful, tolerant, and reject all forms of violence.